Differences and similarities between LC‐MS derived serum fingerprints of patients with B‐cell malignancies. Issue 19 (28th June 2013) - Piszcz, Jaroslaw; Lemancewicz, Dorota; Dudzik, Danuta; Ciborowski, Michal; Arribas, Coral Barbas
<x xml:space="preserve">Abstract</x> Multiple myeloma (MM) and chronic lymphocytic leukaemia (CLL) are closely related B‐cell non‐Hodgkin's lymphomas. MM, a plasma cell malignancy, is the second most common haematopoietic cancer in Western countries, with the median survival time of 3–4 years. CLL, a lymphocyte B malignancy, is the most common leukaemia in Western countries. About 25–30% of all CLL patients do not survive the period of 5 years following diagnosis. Both malignancies are complicated, not fully understood and incurable with the current standard treatment. Biologically, MM and CLL may be preceded by associated precursor conditions, that is, monoclonal gammopathy of undetermined significance for MM and its cellular counterpart and monoclonal B‐cell lymphocytosis for CLL. Similarities and differences in the biology of these malignancies prompted us to evaluate their metabolomics in stages requiring chemotherapy. Fingerprinting of serum metabolites by the use of LC‐MS has never been applied in studies on MM and CLL patients. Obtained results revealed metabolites common for both malignancies (e.g. fatty acids, acylcarnitines, sphingolipids, phospholipids, phenylalanylphenylalanine and isoprene) as well as those which render them different (e.g. lysophosphatidylcholines, monoacylglycerols, aminocaproic acid, phenylacetylglutamine).